Tren Studi Perempuan Selama Transisi Menopause - Sarasati, Budi; Setiasih; Sukamto, Monique Elizabeth (ANIMA Indonesian Psychological Journal, 2024)
This study is a bibliometric analysis with the aim to explore scientific publications related to the psychological well-being of women in the perimenopause transition phase. The analyzed data was sourced from scientific articles indexed by Scopus from 1985 to October 2023. Scientific article search technique was conducted by tracking scientific publication documents in a database through search queries with search string. Analysis results provided four main findings: (1) psychology is not the only scientific discipline that studies issues related to the menopausal transition phase and not the field of study that produces the highest number of scientific publications; (2) publications related to the menopausal transition phase with the highest level of influence in the discipline of psychology are dominated by mental health topics such as depression and sleep disorders; (3) academic interest in studying the menopausal transition phase in psychology is increasing with each publication period; and (4) a diversity of study topics has emerged as interest in studying the menopausal transition phase has increased; however, in the last twenty years, there has been a trend towards stagnation of studies on the topic of perimenopausal depression and decrease of research interest in various dimensions of psychological well-being. The conclusion of this study is that bibliometric metadata of a scientific publication corpus is dynamic, causing metrics to change with time, and that analysis can be utilized to see trends in scientific publications related to the issue of women's physical and psychological health in the menopausal transition phase.